2020
DOI: 10.32890/mjli2020.17.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning as a Mediator in the Relationship Between Peer Learning and Online Learning Satisfaction: A Study of a Private University in Malaysia

Abstract: Purpose – Students’ ability to self-regulate their learning and to learn effectively with peers are indicators of success in the era of the 4th Industrial Revolution. This study investigated whether peer learning helps to influence online learning satisfaction in the presence of self-regulated learning (SRL) as a mediating variable. Methodology - The study adopted a correlational research design to examine the possibility of relationships between these variables. The sample was selected based on proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 0 publications
6
36
0
3
Order By: Relevance
“…For instance, Zimmerman et al (1996) argue that SRL skills enable students to improve their overall learning achievements and their views on self-efficacy as they are more responsible for their learning. In a similar vein, Lim et al (2020) and Zalli et al (2019) found that self-regulation becomes a mediating variable that influences students' satisfaction in the online learning context. Consequently, exploring students' level of SRL has significant importance, particularly in online learning environments that urge students to independently manage their learning progression.…”
Section: Introductionmentioning
confidence: 79%
“…For instance, Zimmerman et al (1996) argue that SRL skills enable students to improve their overall learning achievements and their views on self-efficacy as they are more responsible for their learning. In a similar vein, Lim et al (2020) and Zalli et al (2019) found that self-regulation becomes a mediating variable that influences students' satisfaction in the online learning context. Consequently, exploring students' level of SRL has significant importance, particularly in online learning environments that urge students to independently manage their learning progression.…”
Section: Introductionmentioning
confidence: 79%
“…However, the shift to technology-enabled learning has resulted in the learners reporting a loss of these skills emerging from the interaction with digital mediums and the availability of recorded lectures. This can further be located in the learner-initiated changes towards self-directed learning enabled through digital literacy and knowledge-based community building (Garip et al, 2020 ; Lim et al, 2020 ; Stephen & Rockinson-Szapkiw, 2021 ; Zimmerman & Schunk, 2011 ). If the conventional built spaces were dominated by the centrality of the teacher-instructor, the online learning spaces seem to have foregrounded the significance of knowledge-based communities, peeIpl2uae#r interactions (Altınay, 2017 ; Peters & Romero, 2019 ), and the role of the instructor as a ‘pedagogical-weaver’ (Lee & Tan, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peer learning gained further prominence with online and blended learning modes (Raymond et al, 2016 ) that necessitated the learners to engage in self-regulated learning (SRL) (Garip et al, 2020 ; Stephen & Rockinson-Szapkiw, 2021 ; Zimmerman & Schunk, 2011 ). Studies show that SRL promotes peer interaction and enhances learners’ satisfaction in online and blended learning contexts (Lim et al, 2020 ). SRL is based on the social cognitive theory that perceives learning to be relational, based on the interactions between the learner (self), their behavior, and the learning environment.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, this study utilises the model of online learners' engagement and satisfaction by Kucuk and Richardson (2019) to identify learners' experience in learning during the Covid-19 upheavals. Students' engagement involved the use of resourceful educational platforms, such as Moodle and learning management systems, to assist splendid progress in the students' online learning process (Jalil et al, 2019;Lim et al, 2020a;Lim et al, 2020b). Following several attempts to communicate with students, teachers are being efficiently trained until they master the methods of distribution and accelerate learning through the use of information technology (IT) and the internet in a short period.…”
Section: Literature Reviewmentioning
confidence: 99%